(untitled) (Journal of actual problems of jurisprudence, 2016)
Legislative consolidation and improvement of the Institute of witness immunity is a major step towards strengthening the democratic and moral principles of criminal justice. Despite this, the guarantees of this constitutional principle should clearly work. Namely actual participation of counsel in the interrogation of the witness and assigns to him the additional responsibility to ensure that the rights and legitimate interests of the witness.